2018
DOI: 10.18483/ijsci.1520
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Protective Effect of Moringa oleifera Leaf Extract against Aluminium Induced Liver Damage in Male Albino Wistar Rats

Abstract: Aluminium is a hepatotoxic element that is extensively used in the production of household cookware, storage utensils, water purification and in the preparation of some drugs. Conversely, the leaf extract of Moringa oleifera is hepatoprotective amongst other medicinal and nutritional benefits.The present study evaluated the protective effect of ethanol leaf extract of Moringa oleifera on Aluminium induced hepatotoxicity in male albino wistar rats. Eighteen (18) male albino wistar rats weighing between140 and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 6 publications
5
0
0
Order By: Relevance
“…There was significantly (p < 0.05) higher ALP level between the Aluminium chloride group and the control, indicating that Aluminium chloride may have caused tissue toxicity leading to their leakage into the serum. The present result is in line with Moshtaghie et al (2006) and Akpanyung et al (2018), who reported that Aluminium chloride administration increased ALP. ALP is a polyfunctional enzyme that acts as a transphorylase at alkaline pH, and plays a pivotal role in the mineralization of the skeleton of animals (Zhang et al, 2011), and these may have been compromised.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…There was significantly (p < 0.05) higher ALP level between the Aluminium chloride group and the control, indicating that Aluminium chloride may have caused tissue toxicity leading to their leakage into the serum. The present result is in line with Moshtaghie et al (2006) and Akpanyung et al (2018), who reported that Aluminium chloride administration increased ALP. ALP is a polyfunctional enzyme that acts as a transphorylase at alkaline pH, and plays a pivotal role in the mineralization of the skeleton of animals (Zhang et al, 2011), and these may have been compromised.…”
Section: Discussionsupporting
confidence: 93%
“…ALP is a polyfunctional enzyme that acts as a transphorylase at alkaline pH, and plays a pivotal role in the mineralization of the skeleton of animals (Zhang et al, 2011), and these may have been compromised. As there was no difference with the other test groups compared to the control, it indicates that M. oleifera may have counteracted the activity of the Aluminium chloride which is in line with previous a study (Akpanyung et al, 2018).…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consequently, elevation of LDL-C has a negative impact on the cardiovascular system and could result in cardiovascular events such as arrythmia, cardiac arrest and heart attack (Dayuan and Mehta, 2005). Elevation of LDL-C observed in the present study indicates that administration of theobromine might increase the risk of cardiovascular events (Akpanyung et al, 2018b).…”
Section: Discussionsupporting
confidence: 58%